2014
DOI: 10.1105/tpc.113.114454
|View full text |Cite
|
Sign up to set email alerts
|

The BAF60 Subunit of the SWI/SNF Chromatin-Remodeling Complex Directly Controls the Formation of a Gene Loop at FLOWERING LOCUS C in Arabidopsis  

Abstract: SWI/SNF complexes mediate ATP-dependent chromatin remodeling to regulate gene expression. Many components of these complexes are evolutionarily conserved, and several subunits of Arabidopsis thaliana SWI/SNF complexes are involved in the control of flowering, a process that depends on the floral repressor FLOWERING LOCUS C (FLC). BAF60 is a SWI/SNF subunit, and in this work, we show that BAF60, via a direct targeting of the floral repressor FLC, induces a change at the highorder chromatin level and represses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
85
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 70 publications
2
85
0
Order By: Relevance
“…In addition to promoter regions showing altered nucleosome occupancy in our MNaseSeq study, the ChIP-Seq data also identified characteristic peaks of SWP73B representation in the coding sequences and 39-UTRs of the AS1, AS2, and YAB5, as well as AGL24, LFY, AP1, AP3, and SEP3 genes involved in leaf and flower development, suggesting an overall role of SWP73B-containing SWI/SNF complexes in their transcription (Figures 3C and 3D;Supplemental Figures 7C and 7D). In the shared upregulated ChIP-Seq and MNase-Seq data set, we identified the FLC gene, in which peaks of SWP73B occupancy were also detected in both 59-and 39-UTRs, confirming previous data on the location of SWP73B target sites in this locus (Jégu et al, 2014;Supplemental Figures 7C and 7D). In summary, our comparative transcript profiling and MNase-Seq and ChIP-Seq studies consistently identified a small set of genes that are known regulators of leaf and flower development and show association with SWP73B, in addition to altered nucleosome occupancy in the 59-UTRs and altered transcript levels in the swp73b mutant.…”
Section: The Swp73a and Swp73b Mutations Affect Different Developmentsupporting
confidence: 76%
See 4 more Smart Citations
“…In addition to promoter regions showing altered nucleosome occupancy in our MNaseSeq study, the ChIP-Seq data also identified characteristic peaks of SWP73B representation in the coding sequences and 39-UTRs of the AS1, AS2, and YAB5, as well as AGL24, LFY, AP1, AP3, and SEP3 genes involved in leaf and flower development, suggesting an overall role of SWP73B-containing SWI/SNF complexes in their transcription (Figures 3C and 3D;Supplemental Figures 7C and 7D). In the shared upregulated ChIP-Seq and MNase-Seq data set, we identified the FLC gene, in which peaks of SWP73B occupancy were also detected in both 59-and 39-UTRs, confirming previous data on the location of SWP73B target sites in this locus (Jégu et al, 2014;Supplemental Figures 7C and 7D). In summary, our comparative transcript profiling and MNase-Seq and ChIP-Seq studies consistently identified a small set of genes that are known regulators of leaf and flower development and show association with SWP73B, in addition to altered nucleosome occupancy in the 59-UTRs and altered transcript levels in the swp73b mutant.…”
Section: The Swp73a and Swp73b Mutations Affect Different Developmentsupporting
confidence: 76%
“…In these lines, a reduction of SWP73B transcript level was reported to correlate with dwarfism and enhanced resistance to Agrobacterium tumefaciens-mediated root transformation (Crane and Gelvin, 2007). Recently, these lines were found to show a late flowering phenotype under inductive long-day conditions (Jégu et al, 2014). In addition, a homozygous SALK_113834 line carrying a T-DNA insertion in the SWP73B promoter region has been used in a study to demonstrate the involvement of SWP73B in DNA repair after UV-B treatment (Campi et al, 2012).…”
Section: Identification Of Swp73a and Swp73b Insertion Mutantsmentioning
confidence: 99%
See 3 more Smart Citations